Achieving a Jobs-Housing balance in the Paris region - the potential of reducing car trafic - Marie-Hélène Massot; Emre Korsu (European Regional Science Association (ERSA), 2005)
Many experts believe that the uninterrupted lengthening of trip distances, and especially trip-to-work distances, is carried mostly by urban sprawl combined to growing functional (economic functions/residential functions) and social (high-class residential areas/low-class residential areas) specialization of urban space. According to them, these three dynamics (urban sprawl - functional specialization - social specialization) drag along quantitative and qualitative spatial imbalances between economic and residential functions and these spatial imbalances contribute to widen the distance separating workers' homes and job places, and hence, to lenghten the trips-to-work. On the basis of this diagnosis, the re-establishement of a greater balance, on both quantitative and qualitative grounds, between jobs and housing in different areas of the city is currently emerging as a major issue regarding the car-traffic reducing goal. Making the assumption that the multiplication of long-distance trips occurs as a consequence of greater difficulties encountered by households searching decent housing nearby workplaces, many experts argue that efficient urban policies promoting a diversified housing supply nearby job centres would allow more reasonable commuting distances and that such a return should go forth with a reduction in car traffic. In this paper, through a simulation model based on re-assignment of households closer to their workplaces, we examine the potential of car traffic reduction in the case of the Paris region. More precisely the impact of jobs-housing balance policy is based on a simulation model which states assignment of households located far from their work place within zones located nearer to the work place. The households that are reassigned are those where all workers travel more than a given time-threshold to reach their work place. These households are relocated within a perimeter around either the work place of the head of the household if it is a one worker household or the work place of the female worker if it is a two worker household - this perimeter is defined with reference to a time-threshold (set to 20, 30 or 45 minutes by private car or by public transport). For each type of household (defined according to social status, number of workers and family profile), the type of housing demanded by reassigned households is derived from the structure of housing detained by households that are already located within the perimeter of re-assignment. Three analyses are conducted on the basis of this simulation. According to the different time-thresholds : first, we estimate the total distances saved on home-work trips by private car when households are reassigned. Second, we identify the characteristics of reassigned households (especially social status, number of workers, family profile, residential location, job location, etc.). Third, we estimate the housing offer/demand imbalance after re-assignment (with specific interest for the case of housing for low-income groups).
Keywords: 330